The viability of Mycoplasma iowae at 40 C in Turkey semen - Majid, M. Shah; Rosendal, S. (Oxford University Press, 1985)
Mycoplasma iowae was mixed with turkey semen, incubated at 40 C in a water bath, and sampled at different intervals. The M. iowae remained viable throughout a 48-hr incubation period